PENGARUH KOMPETENSI DAN PERSON ORGANIZATION FIT (PO-Fit) TERHADAP KINERJA MELALUI MEDIASI KOMITMEN ORGANISASIONAL Studi pada Penyuluh Pertanian Dinas Pertanian Tanaman Pangan dan Peternakan Kabupaten Pati - Sudaryanto, Sudaryanto; Rijanti, Tristiana (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to examine and analyze the influence of Competence and Person Organization Fit (PO-Fit) to performance through the mediation of Organizational Commitment on Agricultural Extension in the Department of Agriculture and Animal Husbandry Pati Regency. The total sample of 179 respondents was conducted with a purposive sampling of Agricultural Extension Department of Agriculture and Animal Husbandry Pati regency with sample criteria for Agriculture is an active work and tenure of more than five years. Mechanical testing of the data used in this study include Validity Test, Reliability Test, Coefficient of Determination Test, F Test, Tests of Hypotheses and Mediation. The results showed that Competency positive effect on Commitment Organizational, Person Organization Fit (PO-Fit) positive effect on Commitment Organizational. Competence positive effect on Performance, Person Organization Fit (PO-Fit) positive effect on Performance and Commitment Organizational positive effect on Performance, Organizational Commitment is not a variable that mediates influence of Competence to Performance, Competence direct effect on the Performance and Organizational Commitment is not a variable that mediates influence of Person Organization Fit (POFit) to Performance. Keywords: Competence, Person Organization Fit (PO-Fit), Organizational Commitment, Performance.